2016
DOI: 10.1088/0960-1317/26/11/115015
|View full text |Cite
|
Sign up to set email alerts
|

A miniaturized Rogowski current transducer with wide bandwidth and fast response

Abstract: The miniaturization of the 3D Rogowski current transducer down to the micro-scale is essential for device integration and expansion of its application scope, particularly for 'lab-on-a-chip' systems. However, fabrication of 3D miniaturized Rogowski coils remains challenging as most relative methods still rely on the 2D micromachining process. In this paper, a miniaturized Rogowski coil current transducer was fabricated using an improved femtosecond laser wet etching technology and a metal microsolidification p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Another important application is using the fabricated microchannels or microstructures as the mold for replicating polymer or metal microstructures [92][93][94][95][96] . Chen et al demonstrated the fabrication of polymer planar convex microlens arrays and compound eyes by replication of silica concave microlens arrays, which were fabricated by wet-etching-assisted femtosecond laser modification 94,95 , as the diagram shown in Fig.…”
Section: Wet-etching-assisted Femtosecond Laser Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important application is using the fabricated microchannels or microstructures as the mold for replicating polymer or metal microstructures [92][93][94][95][96] . Chen et al demonstrated the fabrication of polymer planar convex microlens arrays and compound eyes by replication of silica concave microlens arrays, which were fabricated by wet-etching-assisted femtosecond laser modification 94,95 , as the diagram shown in Fig.…”
Section: Wet-etching-assisted Femtosecond Laser Modificationmentioning
confidence: 99%
“…7(b) -7(d). Meanwhile, by injecting of metal or metal alloys into 3D silica microchannels, various complicated metal microstructures are fabricated with large aspect ratios, such as micro-coils with operating bandwidth can be reached to 10 GHz 93 .…”
Section: Wet-etching-assisted Femtosecond Laser Modificationmentioning
confidence: 99%
“…In contrast, femtosecond laser micromachining introduces a "cold" processing approach that minimizes damage to the surrounding area and facilitates ultra-high precision micro-/nanofabrication [55][56][57]. Therefore, femtosecond laser micromachining technology not only fulfills the demands for flexible three-dimensional processing of devices, but also achieves downsizing [58][59][60][61][62][63][64][65], establishing itself as a potent tool for the fabrication of microlenses in compound eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Though it depends on specific system, one can think of currents reaching 100 A and higher within a short time of the microsecond order. Features of existing cur-rent sensors [1][2][3][4][5][6][7][8][9][10][11] are presented in Table 1. In this study, we selected Rogowski coil that features linearity of measurement up to heavy current, small temperature fluctuation, and compatibility with semiconductor processes.…”
Section: Introductionmentioning
confidence: 99%